ANALISIS EFEKTIVITAS, PERTUMBUHAN DAN KONTRIBUSI RETRIBUSI TEMPAT KHUSUS PARKIR TERHADAP PAD DI DINAS PERINDAGSAR KABUPATEN KEBUMEN - Wahyuningsih, Sri; Rahmadiyanti, Ridhani (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2017)
In order to improve the provision of services to the public in the field of parking, environmental arrangement, and order, and as a source of local revenue (PAD), serious and consistent effort is required. In order to achieve the service and implementation of development effectively, each region must be creatively able to create and encourage the increase of local revenue sources. One of the potential sources of Local Revenue (PAD) is from the parking services sector. The purpose of this analysis is to know the level of effectiveness and growth rate of Parking Parking Placement Levies (RTKP) and to know how big contribution of realization of Levy Parking Parking Area (RTKP) to Local Revenue (PAD) in Trade and LLMarket Service Office of Kebumen Regency . The main problem is how the level of effectiveness and growth rate of Parking Parking License (RTKP) and how much contribution of Parking Area Specific Levy (RTKP) to Local Own Revenue (PAD) in 2013-2015 at Trade and Market Service Office of Kebumen Regency. Namely the method of quantitative analysis, the data used are primary data and secondary data. The method of preparation used in this research is descriptive method of analysis. From the result of the analysis of the effectiveness of the realization of the acceptance of Parking Parking Places (RTKP) of the Department of Industry and Trade and Market Management Kebumen Regency can be said to be very effective because the effectiveness criteria is more than 100%. Positive growth with averages of 2014 and 2015 showed a positive growth of 102.125%. And the contribution of the realization of Local Parking Revenue (RTKP) revenue over the period of three years from 2013 to 2015 tends to increase with average showing contribution which is included in medium criterion that is with percentage equal to 21,84%.